2022
DOI: 10.1053/j.ajkd.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Recovery and Death in Critically Ill Patients With COVID-19–Associated Acute Kidney Injury Treated With Dialysis: The STOP-COVID Cohort Study

Abstract: Rationale & Objective Acute kidney injury treated with kidney replacement therapy (AKI-KRT) occurs frequently in critically ill patients with COVID-19. We examined the clinical factors that determine kidney recovery in this population. Study Design Multicenter cohort study. Setting & Participants 4221 adults with COVID-19 not receiving kidney replacement therapy who were admitted to intensive care units at 68 US hospitals with COVID-19 from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 33 publications
3
31
1
Order By: Relevance
“…Patients at the lowest global uid overload quartile had lower D-Dimer, LDH, C-RP and ferritin levels (p<0.001) and tended to have lower need for RRT than the other three quartiles, but it was not statistically signi cant (4.3% vs 9.0% vs 14.1 vs 11.5% for 1 st , 2 nd , 3 rd , and 4 th uid overload quartiles, respectively; p= 0.148). On the other hand, patients at 4 th uid overload quartile had longer hospital stay than the other groups (9 [6-17] vs 9.5 [6-16] vs 9 [6-14] vs 11 [7][8][9][10][11][12][13][14][15][16][17][18] days for 1 st , 2 nd , 3 rd , and 4 th uid overload quartiles, respectively, p<0.001). Figure 3 shows the Kaplan-Meier plots for 28-day mortality according to global uid overload quartiles, and for categorical >1000 cc global volume overload.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients at the lowest global uid overload quartile had lower D-Dimer, LDH, C-RP and ferritin levels (p<0.001) and tended to have lower need for RRT than the other three quartiles, but it was not statistically signi cant (4.3% vs 9.0% vs 14.1 vs 11.5% for 1 st , 2 nd , 3 rd , and 4 th uid overload quartiles, respectively; p= 0.148). On the other hand, patients at 4 th uid overload quartile had longer hospital stay than the other groups (9 [6-17] vs 9.5 [6-16] vs 9 [6-14] vs 11 [7][8][9][10][11][12][13][14][15][16][17][18] days for 1 st , 2 nd , 3 rd , and 4 th uid overload quartiles, respectively, p<0.001). Figure 3 shows the Kaplan-Meier plots for 28-day mortality according to global uid overload quartiles, and for categorical >1000 cc global volume overload.…”
Section: Resultsmentioning
confidence: 99%
“…Acute Kidney Injury is one of the most common complications of Covid-19 and it has been associated with increased risk of death, prolonged stay in hospital, and need for RRT 2,3,14 . Although age, male sex, and previous uncontrolled comorbidities, such as cardiovascular disease, diabetes and CKD, have been independently associated with worst outcomes among patients with Covid-19 and AKI, few of them are relatively modi able during hospitalization that could improve prognosis 7,[14][15][16][17][18][19][20][21][22][23][24][25][26] . Likewise, data from previous studies have only focused on clinical and biochemical characteristics and have not widely analyzed patient's volume status in non-acute heart failure context and/or previously treated with RRT 6,15,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to our results, Al Sulaiman et al found that 46% of their patients had AKI [ 18 ]. Similarly, a large multicenter study in the US with 4221 critically ill patients found that AKI occurred in 56% of their patients [ 38 ]. Several studies have proposed the mechanisms of AKI development in COVID-19 patients, which include a higher level of soluble tumor necrosis factor, stimulation of inflammatory mediators and cytokine storms, which can cause a microvascular injury and AKI; moreover, the virus can target angiotensin-converting enzyme 2, which is found in the kidney, and can even directly infect the kidney [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed a systematic search in PubMed to identify recently published large cohort studies related to AKI in patients with COVID-19. We used the search terms “Coronavirus”, “COVID-19”, “SARS-CoV-2”, “acute kidney damage”, “acute kidney injury”, “AKI” and found that the incidence of AKI was higher in severe COVID-19 patients and AKI was strongly associated with high mortality ( Table 1 ) ( Bell et al., 2021 ; Chen et al., 2021 ; Jewell et al., 2021 ; Kilis‐pstrusinska et al., 2021 ; Marques et al., 2021 ; Procaccini et al., 2021 ; Rahimzadeh et al., 2021 ; Scarpioni et al., 2021 ; Sullivan et al., 2021 ; Strohbehn et al., 2021 ; Wan et al., 2021 ; Hung et al., 2022 ; Hsu et al., 2022 ; Sindhu et al., 2022 ). Many possible mechanisms for COVID-19-induced kidney injury have been proposed, including the direct kidney injury mediated by the combination of virus and ACE2.…”
Section: Introductionmentioning
confidence: 99%